SERUM OESTRADIOL -17Ã¢ AND PROGESTERONE PROFILE IN HAMPSHIRE GILTS FOLLOWING SYNCHRONIZATION OF OESTRUS BY PGF 2âˆ ANALOGUES - S. SINHA3, H. KONCH1; ARUP DUTTA K. K. BARUAH (Indian Journal of Animal Production and Management, 2017)
Following synchronization of oestrus by PGF2-âˆ analogue, serum oestradiol-17Ã¢ and progesterone concentration during different stages of gestation were carried out in a total 18 pubertal Hampshire gilts reared in the Base Pig Breeding Farm, Department of Animal Husbandry and Veterinary, Government of Assam, Khanapara,Guwahati. The pubertal gilts were divided in to three groups viz. Group I and II as treated and Group III as control. Gilts of Group I received 5ml Iliren during luteal phase of cycle whereas gilts of Group II received Serum oestradiol -17Ã¢ and progesterone profile in Hampshire gilts two injection of 5ml Iliren at 11 days apart. The mean serum oestradiol-17Ã¢ and progesterone showed significantly (P<0.01) higher and lower concentration respectively in all gilts of three experimental groups on the day of oestrus as compared to the concentration obtained during different days of gestation. During gestation, a significantly lower level of mean serum oestradiol-17Ã¢ and higher level of progesterone concentration was recorded whereas on the day of farrowing, the concentration again significantly increased and decreased for serum oestradiol-17Ã¢ and progesterone respectively in all the gilts of treated and control group. Key Words : Oestradiol-17Ã¢, Progesterone, PGF2-âˆ analogue, Gestation, Synchronization.